The Motivation of Communication to Consumer Perception in Bangkok - เชาว์แก้ว, กมลชนก; พินิจสุวรรณ์, จีรนันท์; ศรีสังข์, ดวงหทัย; วงศ์หงส์, ธันยากร; ยลโต, พินทุสร; ไทยสม, รุ่งทิพย์ (Journal of Industrial Business Administration, 2019)
This research is for to learn about The Motivation of Communication to Consumer Perception in Bangkok. The scope of the research and the example group is the people who live in Bangkok. According to the Institute for Population and Social Research of Mahidol University, Bangkok is the number one country of the population in Thailand. This research is focusing on the factor such as demography, behavioral science and communication of motivation in a decision to receive messages that effect to consumer perception. To search the information, us the questionnaires to the example group 400 unit, then analyze and summarize. The results are the customer is the female who lives in Bangkok 248 persons, 62 percent. Are in the age range 20-29 years about 158 persons, 39.50 percent, bachelor's degree education 248 persons, 62 percent and earning 10,000-15,000 baht 82 persons, 20.50 percent. The proving to the hypothesis test found that a brand's reputation has an effect on Communication of Motivation in a decision to receive messages that effect to consumer perception in Bangkok metropolitan.